Increase of cervical cancer incidence in Sweden in relation to screening history: population cohort study. (2nd August 2020) - Wang, Jiangrong; Andrae, Bengt; Strander, Björn; Sparén, Pär; Dillner, Joakim
Abstract: Background: Cervical cancer incidence in Sweden decreased from 24/100, 000 in 1965 to 8/100, 000 in 2011, but has from 2014 increased to 11/100, 000. The increase appears to correlate to screening history. We perform a study of the cancer risk change in relation to screening history over two screening rounds to verify the correlation. Material and methods: We studied the cohorts of all 3, 047, 850 individual women living in Sweden in each year from 2002–2015. Registry linkages between the Total Population Register, the Swedish National Cervical Screening Registry, the Swedish Cervical Cancer Audit database and the National Quality Register for Gynecological Cancer, defined the incidence rates of invasive cervical cancer comparing time periods 2002–2013 to 2014–2015, in women whose screening history in 2 screening intervals prior to each year were either (i) adequately screened with normal results (almost exclusively cytology, 52% of the population) or (ii) unscreened (13% of the population). We also investigated the incidence increase by time since a normal smear performed in 2002–2012. Results: Among women adequately screened with normal results there was a strong incidence increase in 2014–2015 compared to previous years (Incidence rate ratio (IRR) = 1.59, 95%CI = 1.36–1.85), but no significant increase among unscreened women (IRR = 1.09, 95%CI = 0.94–1.27). There was no increase in incidence 0–2.5 years after a normal smear over the study period (IRR = 1.04, 95% CI = 0.88–1.24), but a strong increase 3–4 years after a normal smear since year 2009 (IRR = 1.52, 95% CI = 1.25–1.84). Conclusion: The results suggest that the overall increase is associated with an increased cancer risk in women adequately screened with normal cytological results. Possibly, precursor lesions missed in one screening round might result in detection of early stage invasive cancer in the subsequent screening.